Chromosomal analysis of the leptodactylids Pleurodema diplolistris and Physalaemus nattereri (Amphibia, Anura) - Lourenco, Luciana B.; Nascimento, Josiane A. A.; Andrade, Gilda V.; Rossa-Feres, Denise C.; Recco-Pimentel, Shirlei M. (Brill Academic Publishers, 2006)
Detailed characterizations of the karyotypes of the Brazilian leptodactylid frogs Pleurodema diplolistris, the only species of Pleurodema not studied cytogenetically so far, and Physalaemus nattereri, a species in the Ph. biligonigerus group, are presented. Both karyotypes had 2n = 22 and their chromosomes had a very similar morphology, except for pair 11, which was metacentric in Pl. diplolistris and telocentric in Ph. nattereri. The localization of nucleolar organizer regions (NORs) and heterochromatic bands allowed the differentiation of chromosomes that were morphologically indistinguishable between these species, such as pairs 1, 3 and 10, which showed interstitial C-bands in Ph. nattereri, and pair 8, that had an NOR and an adjacent C-band in Pl. diplolistris. Pair 8 also has NOR-bearing chromosomes in many other Pleurodema species. However, in these species, the NOR is located proximal to the centromere on the short arm, while in Pl. diplolistris it occurred distally on the long arm, a condition that may be considered a derived state. In Ph. nattereri, the NOR occurred on chromosome I 1 and differed from the other species of the Ph. biligonigerus group. In contrast, C-banding revealed a heterochromatic block near the centromere on the short arm of pair 3, a characteristic common to all members of this group of Physalaemus.
Keywords: Anura; Cytogenetics; heterochromatin; Leptodactylidae; NOR